Evaluación de proyectos de ingeniería ambiental - Reid, George W. (My University, 2014)
1.Areas of conflict. 2. industry and government. 3. Government objective. Technology/management. 5. Assessment practicum. 6. legal basis
Keywords: EVALUACION; PROYECTOS; INGENIERIA AMBIENTAL